Comparative Evaluation and Environmental Importance of Removal of Methyl Orange by Photocatalysis and Mgo Nanoparticle - Shivaprasad H, Shivaprasad H; D. P. Nagarajappa, D. P. Nagarajappa (Current world environment, 2022)
The treatment of the coloured effluents is gaining huge attention in recent years. Use of nanomaterials to treat wastewaters have been the subject of active research and development worldwide in recent years. To outcome of experimental findings on degradation of methyl orange by MgO nanoparticle through adsorption and nano photocatalysis are presented in this paper. The effects of pH, stirring/contact/irradiation time, dye concentration, adsorbent dosage is investigated. At the optimum conditions of experimentation, 63.9% and 72.3% of methyl orange removal by nano photocatalytic and adsorption process are recorded. The analysis of adsorption isotherms indicated that the experimental data fitted very will built both Langmuir and Freundlich isotherms.